Transformasi Bentuk Flora ke Dalam Elemen Dekorasi Interior Menggunakan Teknik Makrame - Adiro, Putri Aurum; Zubaidah, Zubaidah (Al-DYAS, 2023)
Among the people today there are still many of them who are non sensitive to the surrounding environment, from here the author provides solutions, by utilizing various media and techniques in creating fine arts, one of which is textile crafts using macrame techniques, as a reminder of the community to the environment, as well as an idea / source of inspiration for entrepreneurial ideas within the scope of the creative industry by visualizing the shapes of flora. Like the basic shape of flower petals, leaves and tree branches, making it a decorative work that is in demand by various circles. The method of creating the author using is a method that has been proposed in the art consortium carried out in stages, namely the preparation stage by searching for information, elaboration by analyzing problems, synthesis of setting ideas, realization ofsetting ideas, realization of concepts by making macrame works and stages of completion by conducting joint exhibitions. In this final work, the author produced seven interior decoration works with a wide variety of sizes and shapes, symmetrical, asymmetrical, circular and square.